2014
DOI: 10.1021/ed500099h
|View full text |Cite
|
Sign up to set email alerts
|

Making Data Management Accessible in the Undergraduate Chemistry Curriculum

Abstract: In the age of "big data" science, data management is becoming a key information literacy skill for chemistry professionals. To introduce this skill in the undergraduate chemistry major, an activity has been developed to familiarize undergraduates with data management. In this activity, students rename and organize cards that represent "data files" associated with experiments they completed in a previous course. This activity reveals differences between the way novices (students) and experts (librarians and fac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 4 publications
0
15
0
Order By: Relevance
“…In the interviews, multiple students identified "Excel skills" or "increased stats skills" as being among the most important skills they had gained. Incorporating data management training as a critical part of undergraduate curricula is gaining acceptance, but this training remains relatively rare (Reisner et al 2014). Perhaps because training on these skills can be absent from undergraduate science education, some of the LUGNuts students indicated that they applied their emerging information management skills almost immediately in other classes.…”
Section: Student Perspectivesmentioning
confidence: 99%
“…In the interviews, multiple students identified "Excel skills" or "increased stats skills" as being among the most important skills they had gained. Incorporating data management training as a critical part of undergraduate curricula is gaining acceptance, but this training remains relatively rare (Reisner et al 2014). Perhaps because training on these skills can be absent from undergraduate science education, some of the LUGNuts students indicated that they applied their emerging information management skills almost immediately in other classes.…”
Section: Student Perspectivesmentioning
confidence: 99%
“…While most of the initiators of library data services have been large research universities (Antell et al, 2014; Cox and Pinfield, 2014; Heidorn, 2011; Soehner et al, 2010; Tenopir et al, 2012, 2013, 2014), there is a growing body of literature about data services at Master’s universities and PUIs (Goldstein and Oelker, 2011; Scaramozzino et al, 2012; Shorish, 2012; Stamatoplos et al, 2016; Toups and Hughes, 2013), and about how outreach efforts related to data literacy and data management may be implemented with undergraduate students at a range of institution types (Ball and Medeiros, 2012; MacMillan, 2010; Mooney et al, 2014; Piorun et al, 2012; Qin and D’Ignazio, 2010; Reisner et al, 2014; Shorish, 2015; Stephenson and Caravello, 2007; Strasser and Hampton, 2012; Zilinski et al, 2014). Librarians at PUIs have argued that while resources may be limited at smaller institutions, the same imperatives to act as data stewards and to transmit best practices apply (Shorish, 2012).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Additionally, there have been several efforts to develop LIS curriculum and eScience and/or scientific data management; however while this curriculum is in place to educate students and there is demand for experts, there is still yet to be a unified title for the scientific data specialization [13]. Domain science educators have indicated that the majority of the work in data literacy has focused on graduate students, while there is a real need for similar data literacy instruction to include undergraduate students [14].…”
Section: The Emergence Of Library and Information Science Data Curriculamentioning
confidence: 99%